Zig Zag Book Media Based on Augmented Reality “BERUANG” on Mathematics Learning of Classroom Building Material V Elementary School - Amelia Nurhaliza Putri; Elok Fariha Sari (LPPM Undiksha, 2025)
The learning process is still less active, and students' interest in learning spatial figures is relatively low. One of the causes is the limited use of interesting learning media. This study aims to develop and test the feasibility, practicality, and effectiveness of the Augmented Reality-based Zig Zag Book learning media named